Discourse analysis : a resource book for students - Jones, Rodney H. (Routledge English Language Introductions, 2012)
"Routledge English Language Introductions cover core areas of language study and are one-stop resources for students. Assuming no prior knowledge, books in the series offer an accessible overview of the subject, with activities, study questions, sample analyses, commentaries and key readings--all in the same volume. The innovative and flexible 'two dimensional' stricture is built around four sections--introduction, development, exploration and extension --which offer self-contained stages for study. Each topic can also be read across these sections, enabling the reader to build gradually on the knowledge gained. Each book in the series has a companion website with extra resources for teachers, lecturers and students"